Desamonificação como tratamento de digestato de biodigestor de lodos da suinocultura para a remoção de nitrogênio - Chini, Angélica (2019)
Brazilian swine production, in industrial scale, works in a concentrated animal feeding opera-tion (CAFO) model, which is characterized by the large animal concentration in small produc-tive areas. Consequently, there is a high effluents generation volume that is rich in nutrients (mainly nitrogen and phosphorous) and needs a correct management. Thus, biological nutri-ents removal processes are widely used. Anaerobic digestion is the main technology used in agroindustry wastewater to remove organic matter. For nitrogen removal, there are conven-tional process (nitrification/ denitrification) and advanced processes, such as deammonifica-tion. This research was divided into two steps: the first was to study the solid-liquid separa-tion (SLS) process of swine manure as digestate to biodigester. The processes tested were: settling, centrifugation and chemical flocculation. The results showed the possibility of apply-ing different SLS processes in the digestate as a pretreatment for solids and carbon reduc-tion. The best process performance for this effluent, aiming subsequent nitrogen removal from liquid fraction by deammonification, was centrifugation reaching a carbon and total sol-ids removal of 90% and 83% respectively. The second step, was aimed to study the C/N ra-tio impact (using digestate obtained in previous step) over the nitrogen removal efficiency and in the microorganism community in a deammonification reactor. It was possible to apply the digestate in deammonification process with average efficiency above 50% in all experi-mental phases. The best C/N ratio tested was 0.5 and carbon concentration of 0,57 gTOC L-1 d-1, with a maximum nitrogen removal efficiency of 72%. Changes in the microorganism community were also observed. The results obtained in this thesis can support wastewater treatment plants to achieve higher yields, through the use of SLS fractions and for develop-ment of a full scale deammonification systems.